Modern African drama : backgrounds and criticism - Jeyifo, Biodun, 1946- (New York : W.W. Norton, 2002)
Presents eight twentieth-century plays from seven African countries, along with explanatory notes and over thirty background writings and works of criticism
The fate of a cockroach / Tawfik al-Hakim -- Intelligence powder / Kateb Yacine -- Sizwe Bansi is dead / Athol Fugard, John Kani & Winston Nthsona -- Death and the king's horseman / Wole Soyinka -- A collision of altars / Tsegaye Gabre-Medhin -- The dilemma of a ghost / Ama Ata Aidoo -- I will marry when I want / Ngugi wa Thiong'o and Ngugi wa Mirii -- Esu and the vagabond minstrels / Femi Osofisan
Includes bibliographical references and index
1
Keywords: African drama (English); African drama (English) -- History and criticism; Theater -- Africa